3x+26=-1

Simple and best practice solution for 3x+26=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+26=-1 equation:


Simplifying
3x + 26 = -1

Reorder the terms:
26 + 3x = -1

Solving
26 + 3x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + 3x = -1 + -26

Combine like terms: 26 + -26 = 0
0 + 3x = -1 + -26
3x = -1 + -26

Combine like terms: -1 + -26 = -27
3x = -27

Divide each side by '3'.
x = -9

Simplifying
x = -9

See similar equations:

| (9x^2)+(30x)=144 | | (3x^2)+(10x)=144 | | (-2x^3)(-2x^2)= | | 12m+10n-21=0 | | (-2a^3*1b^2)(-2a^2*1b^3)= | | 4x^2+8x-1=0 | | 0.7x^2+3.7x+1=0 | | 5X^2-32X+36=0 | | N-26=9 | | 26-n=9 | | 12x-4=4x+4 | | 1.5n=75 | | y=-7x+1 | | m-1.8=6 | | 6x+1=4x+3 | | 81=3n | | 0.9-x=1 | | x^3+18x^2+71x+40=0 | | u^2-u-7=0 | | -14=7x | | -15=-5x | | 4X^3-18X^2+16X+3=0 | | -8=x+12 | | 20+8q=-42 | | 21+x=-9 | | -16=x+25 | | x-7.9=3.8 | | 2(x+6)=4x-6 | | n^4+2n^3-n^2-2n=0 | | a-7=-3 | | -7-6=21-2x | | 240=22r+r^2 |

Equations solver categories